Cortical function in amyotrophic lateral sclerosis. A positron emission tomography study. - Kew, J; Leigh, P; Playford, E; Passingham, R; Goldstein, L; Frackowiak, R; Brooks, D (1993)
Positron emission tomography was used to measure regional cerebral blood flow (rCBF) in 12 patients with amyotrophic lateral sclerosis (ALS) and six age-matched controls. Scans were performed at rest, and while subjects performed stereotyped and freely selected movements of a joystick with their right hand. Statistical parametric mapping was used to determine significant differences in rCBF between the two groups at rest and during activation. The ALS group showed no significant difference in global cerebral blood flow at rest compared with controls. However, rCBF at rest was significantly (P < 0.01) reduced in the ALS group in the primary sensorimotor cortex, the lateral premotor cortex, the supplementary motor area, the anterior cingulate cortex, the paracentral lobule and the superior and inferior parietal cortex. Comparison of the increase in rCBF caused by freely selected joystick movements over the resting state between the two groups of subjects showed significantly (P < 0.001) greater activation in ALS patients in the ventral third (face area) of the contralateral primary sensorimotor cortex and in the adjacent contralateral ventral premotor and parietal association cortices; significantly (P < 0.01) greater activation of the contralateral anterior insula and the ipsilateral anterior cingulate cortex (dorso-caudal area 24) was also present in ALS patients. When a comparison of the rCBF response to the free selection task with that to the stereotyped task was performed between the two groups of subjects, ALS patients showed significantly impaired (P < 0.01) activation of the rostral anterior cingulate cortex (area 32), medial prefrontal cortex (area 10), left parahippocampal gyrus and retrosplenial cortex. The pattern of reduced rCBF at rest in ALS patients probably reflects a combination of neuronal loss in all areas of cortex projecting through the pyramidal tract together with loss of projections from the sensorimotor cortex to the motor association areas. The expansion of the upper limb output zone of the sensorimotor cortex in ALS patients during contralateral upper limb movement may represent cortical reorganization in response to Betz cell loss or corticospinal tract disruption. Abnormal recruitment of non-primary motor areas may also represent functional adaptation to a corticospinal tract lesion. Focally impaired activation of the medial prefrontal cortex and parahippocampal gyrus in ALS patients during the process of internal generation of movement could underlie the frontal lobe cognitive deficits reported in previous neuropsychological studies of ALS.